Efficacy, safety, and adverse effects of finasteride and dutasteride in treating benign prostatic hyperplasia: A retrospective cohort study - Wishyar Jamal Al-Bazzaz (Zanco Journal of Medical Sciences)
Background and objective: Symptomatic benign prostatic hyperplasia (BPH) results in several symptoms including the lower urinary tract symptoms. Consequently, BPH may affect the bladder and finally the kidneys. There are various pharmacological options for the treatment of BPH including 5-Alpha Reductase Inhibitors (5-ARIs) (finasteride or dutasteride). Recent researchers have demonstrated that using 5-ARIs for treating BPH may have unfavorable adverse effects. Therefore, this study aimed to compare finasteride and dutasteride in terms of their efficacy, safety, and adverse effects.